Introduction To Themed Issue World Heritage: Cultural Resource Management Giving Asia-pacific A Sense Of Place - Blundell, David (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Cultural resource management (CRM) is about conservation and sustainability of tangible and intangible aspects of culture. Asia-Pacific cultural sites are under consideration for international recognition to safeguard as a place of value for humanity, as well as places where people live, raise children, build their society, and protect environments.1 Who manages cultural resources? They are: policy administrators, politicians, local communities, academics and environmentalists. This provides a point of departure for thinking about our landscapes and artifacts. I have often thought the idea of world heritage is linked to European origins with the concept of heritage sites coming as a result of the European Enlightenment and the Age of Reason. According to Dario Gamboni (professor at the Institute of Art History of the University of Amsterdam), since the French Revolution, our idea of "world heritage" is more recent, stemming from the 20th century. Gamboni cites in his article for Conservation that French author and statesman, André Malraux wrote in 1957, "for a long time, the worlds of art were as mutually exclusive as were humanity's different religions" drawing our attention to civilisations having their own "holy places" being listed for humanity. Malraux further observed that for the first time, "dying fetishes have taken on a significance they never had before, in the world of the images with which human creativity has defied the passage of time, a world which has at last conquered time" (Gamboni, 2001).